Complex and interactive effects of ocean acidification and warming on the life span of a marine trematode parasite. Issue 13 (December 2019) - Franzova, Veronika A.; MacLeod, Colin D.; Wang, Tianxin; Harley, Christopher D.G.
Graphical abstract: Highlights: Functional and absolute life spans of cercariae were differentially affected by simulated ocean acidification and warming. High temperature negatively affected functional life span, suggesting warming may reduce the temporal transmission window. Warming and acidification reduced absolute life span, which may modify the role of cercariae as a food resource in future. The effect of acidification on cercarial life span was highly dependent on temperature. Abstract: Human activities have caused an increase in atmospheric CO2 over the last 250 years, leading to unprecedented rates of change in seawater pH and temperature. These global scale processes are now commonly referred to as ocean acidification and warming, and have the potential to substantially alter the physiological performance of many marine organisms. It is vital that the effects of ocean acidification and warming on marine organisms are explored so that we can predict how marine communities may change in future. In particular, the effect of ocean acidification and warming on host-parasite dynamics is poorly understood, despite the ecological importance of these relationships. Here, we explore the response of one himasthlid trematode, Himasthla sp., an abundant and broadly distributed species of marine parasite, to combinations of elevated temperature and p CO2 that represent physiological extremes, pre-industrial conditions, and end of century predictions. Specifically, we quantified the life span of the free-living cercarial stage under elevated temperature and p CO2, focussing our research on functional life span (the time cercariae spend actively swimming) and absolute life span (the period before death). We found that the effects of temperature and p CO2 were complex and interactive. Overall, increased temperature negatively affected functional and absolute life span, e.g. across all p CO2 treatments the average time to 50% cessation of active swimming was approximately 8 h at 5 °C, 6 h at 15 °C, 4 h at 25 °C, and 2 h at 40 °C. The effect of p CO2, which significantly affected absolute life span, was highly variable across temperature treatments. These results strongly suggest that ocean acidification and warming may alter the transmission success of trematode cercariae, and potentially reduce the input of cercariae to marine zooplankton. Either outcome could substantially alter the community structure of coastal marine systems.